Clinical Application of the Concept of Snigdha and Ruksha Sweda (AYUSHDHARA, 2023)
Sweda Karma is included under Purvakarma of Panchakarma. Swedana helps to remove stiffness, heaviness, coldness of the body and makes the body to perspirate. It also helps to convert the Doshas in a form so that, they can be removed from the body through Vamana and Virechana. Ayurvedic classics have described a wide range of Swedas which are classified into different categories depending upon various factors. One of those classifications made based on Guna of the Sweda Dravya which plays an important role in pacifying the Dosas. Guna means quality or property which has inseparable relationship with the Dravya. Gunas are 41 and classified into 4 types. They are Artha Gunas - 5; Gurvadi Gunas - 20; Atma Gunas - 6; Paradi Gunas - 10. But for treatment purpose, Gurvadi Gunas are widely used. Among Gurvadi Gunas like Guru, Laghu, Sita, Ushna, Snigdha, Ruksha, Slakshna, Khara etc., Snigdha - Ruksha properties have a very important role in Swedana. Charaka also classified Sweda based on Snigdha - Ruksha properties. The goal of the study is to collect various references of the drugs mentioned for Sweda and categorize them based on their Snigdha and Ruksha property so as to use them appropriately for therapeutic purposes.